WAYS TO IMPROVE STRATEGIC MANAGEMENT OF REGIONAL TOURISM - Jo'raeva Feruza Jumaqulovna (Scholars Digest Publishing, 2023)
The realm of regional tourism is a multifaceted tapestry woven with cultural heritage, breathtaking landscapes, and unique experiences. As tourism becomes an increasingly vital economic sector, the need for effective strategic management in regional tourism has never been more critical. Strategic management acts as a compass, guiding destination authorities, stakeholders, and businesses towards sustainable growth, enhanced visitor experiences, and socio-economic benefits for local communities. This article will provide in-depth insights into each of the mentioned strategies and approaches, offering practical guidance and real-world examples to support regional tourism stakeholders in their pursuit of excellence in strategic management.
Keywords: strategic management, regional tourism, tourism industry, destination management, stakeholder engagement, market research, competitive analysis, marketing strategies, collaboration and partnerships, sustainable tourism.